ATEACHERS’ STRATEGIES IN TEACHING VOCABULARY TO DEAF STUDENTS AT SLB-B KARYA IBU PALEMBANG - Husnaini husna; Sindy Kalora (Universitas Muhammadiyah Lampung, 2023)
The purpose of this study was to determine the teacher's strategy in teaching vocabulary to deaf students. This participants are two teachers of SLB-B Karya Ibu Palembang by using purposeful sampling. This study is case study design. Interview was used to collect data of the study. The interview was administered to two teachers of English subject of SLB-B Karya Ibu Palembang. The data obtained from the interview were analyzed by using thematic analysis. The results of the study showed that the teacher used strategy of (1) using visual media such as pictures and sign language, (2) using audio-visual media like flim, and (3) drilling such as pronouncing the word repeatly and showing the pictures repeatly